Effects of zinc oxide nanoparticles on the expression of zinc transporter 1-4 genes in the hippocampus of male rats under acute stress - Maede NILECHI; Akram EIDI; Hamid GALEHDARI; Mahnaz KESMATI (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
Zinc transporters (ZnT) and ZIP proteins maintain Zinc homeostasis in the live organisms. On the other hand, the impacts of zinc oxide nanoparticles (ZnO NPs) on the expression of the Znt genes in biological systems were not clear yet. So that in this experimental study we have tried to find the eff ects of ZnO NPs on Znt1-4 genes expression in the hippocampus of male rats under acute stress. Adult male rats were divided into groups of control and treated with 5 or 10 mg/kg of ZnO NPs alone and under acute restraint stress for 90 min. The changes in the expression of the selected genes were monitored using real-time qRT-PCR. The ZnT4 protein expression also was measured by Western blotting. Real-time qRT-PCR expression analysis revealed that the Znt1 gene expression was up-regulated in the stress group, while the expression of the Znt1 and Znt4 genes was significantly upregulated in the group receiving 10 mg/kg of ZnO NPs. Furthermore, in the ZnO NPs 10 mg/kg group under stress, the Znt2 gene expression was down-regulated, while the Znt4 gene expression was up-regulated. Moreover, the levels of ZnT4 protein were significantly increased after 10 mg/ kg of ZnO NPs injection in the stress and normal groups. According to these results ZnO NPs administration can cause changes in the expression of a number of zinc transporter genes under stress conditions and increases the ZnT4 protein level. Therefore, this is a valuable approach for forecast investigation in biomedicine and pharmacogenetics studies.